Intervenciones de enfermería y su relación con la prevención de úlceras por presión en pacientes ingresados en unidad de cuidados intensivos Hospital Liborio Pachana Sotomayor. Santa Elena, mayo – septiembre 2019 - Chila Aguilar, Erika Katherine (2019)
Introduction: Pressure ulcers constitute a problem common to all countries and health care levels; they affect people of all age groups and produce high costs both at the level of individual and family suffering and at the socioeconomic level of resource consumption. Objective: To establish the relationship between nursing interventions and the prevention of pressure ulcers in patients admitted to the Intensive Care Unit of the Liborio Pachana Sotomayor Hospital, in the province of Santa Elena, in the period from May to September 2019. Methodology: Field study, exploratory, descriptive, cross-sectional, with a qualitative-quantitative approach. Intentional non-probabilistic sampling was performed according to inclusion and exclusion criteria, consisting of 105 patients with pressure ulcer. Results: From the total sample it was evidenced that it was represented by people over 65 (26.6%), female (51.4%), with secondary education level (57.1%). Overweight (47.6%), cardiovascular disease (20.9%), physical limitation (54.2%) and urinary incontinence (62.7%) were identified as risk factors. Conclusions: Nursing interventions related to education and providing information to patients and family members are of important value, however they are not regularly complied with by nurses, a factor that may be negatively influencing the patient's recovery.